Pattern of lipid alterations in subclinical hypothyroidism: response to Levothyroxine replacement - Nazir Ahmad Pala; Mohd Ashraf; Badrinath Bhoughal (International Journal of Medical Research and Review, 2017)
Objectives: (1) To assess the association of subclinical hypothyroidism (SCH) and lipid profile (2) To quantify the effect of thyroxine treatment on lipid profile.Methods: In a non-randomized matched design, 320 patients who were detected to have SCH and 180 euthyroid controls, matched for age and BMI (body-mass index), werestudied for lipid parameters. Subjects with SCH were further subdivided on the basis of their thyroid functional status: SCH with TSH≤10.0 mIU/L (SCH-1) and SCH with TSH>10 mIU/L (SCH-2). Subjects in SCH-2 group were started on thyroxine replacement and were followed up after 3 months with a repeat lipid profile.Results: Mean total cholesterol (TC) and low-density lipoprotein (LDL) levels were higher and mean high-density lipoprotein (HDL) significantly lower in SCH (SCH-1 and SCH-2) compared to euthyroid controls, but there was no statistically significant difference in the mean triglyceride (TG) levels. Subjects in SCH-2 group had significantly higher mean LDL and lower mean HDL compared to SCH-1 group. There was a significant reduction in mean TC and LDL and increase in HDL after treatment with thyroxine, while there was no significant difference among the mean TG levels.Conclusion: Subclinical hypothyroidism is associated with TSH dependent rise in TC and LDL and fall in HDL compared to controls. Achieving euthyroid status with thyroxine has a favourable effect on lipid profile